Effect of sowing date, temperature and relative humidity on the incidence of net blotch of barley - and S.K. SINGH, RAJENDRA PRASAD*, H.C. SINGH (Indian Phytopathology, 2002)
Experiments conducted during NIb; 1996 and 1997 with six varieties of barley at three sowing dates indicated that the intensity of net blotch was reduced significantly, when the crop was sown on 25 October as compared to late sowings of 14 November and 4 December. However, the interaction effects of variety with different sowing dates and varieties were non-significant. The disease appeared in second week of January with a peak severity towards February end to March. Because of least disease intensity, grain yield (26.33 quintal! ha) was significantly higher in early (25 October) sown crop. Variety ’Azad’ produced the highest grain yield amongst the six varieties evaluate.